Pengaruh Kenaikan Harga Bahan Bakar Minyak (BBM) Terhadap Pendapatan Grab Bike di Kabupaten Mamuju - Asri, Rini; Yati Heryati; Supriadi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The rise in fuel prices has significantly increased operational costs for public transportation, particularly affecting online ride-hailing services such as Grab Bike in Mamuju Regency. This study aims to analyze the impact of fuel price increases on the income of Grab Bike drivers. A quantitative approach was employed using primary data collected through questionnaires distributed to a sample of 95 drivers, determined using the Slovin formula and purposive sampling. Data analysis included instrument validity and reliability testing, partial t-test, simple linear regression, correlation analysis, and the coefficient of determination (R²). The results indicate that fuel price increases have a significant effect on driver income, with a t-value of 4.362 exceeding the critical t-table value of 1.66159 and a significance level of 0.000 < 0.05. The correlation coefficient (R) of 0.825 demonstrates a very strong relationship, while the R² value of 78.1% shows that variations in driver income are largely explained by changes in fuel prices, with 21.9% influenced by other factors. These findings highlight the critical role of fuel price fluctuations in shaping the economic sustainability of Grab Bike drivers, suggesting the need for further investigation into external factors affecting online transportation income.